Душа невесты: повести / Э. Ленхард, Д. Галлагер ; пер.с англ. : А. Мельник - Ленхард Элизабет (Зачарованные, 2004)
Экземпляры: 7ф. (27.03.07г.) / Инвентарный номер: 42857 / Цена: / Сис.шифр: 84 / Авт.знак: Л 46 / ББК: 84